Changing workforce requirements need paradigm shift in education - Turcsányi-Szabó Márta (ЗУІ ім. Ференца Ракоці ІІ, 2025)
Abstract. Throughout history, Industry, Society, Technology, and Education have influenced each other in profound ways. Industry drives societal change. Each industrial revolution reshaped the economy and job market, leading to urbanization, new social classes, and shifts in cultural norms. Society shapes technology. Societal needs and challenges drive technological innovation. Technology transforms education, as technological advancements have continuously expanded access to knowledge and learning methods. Formal education systems have always adapted to provide skills needed for the evolving job market [1]. The development of the web and learning methods has been closely intertwined, with advancements in internet technology directly impacting education. The evolution of the Web and Learning highlights a shift from static, one-way education to dynamic, AI-powered, personalized learning experiences. At first education was limited to classrooms and textbooks, with the web acting as a digital library for reference. Then the internet became interactive, leading to e-learning, online courses, and global knowledge sharing. AI and big data transformed learning into an adaptive, personalized experience, ensuring that students receive tailored content, real-time feedback, and immersive simulations [2].
Keywords: workforce demands; educational reform; paradigm shift